2019
DOI: 10.3390/atmos10100577
|View full text |Cite
|
Sign up to set email alerts
|

Past and Projected Weather Pattern Persistence with Associated Multi-Hazards in the British Isles

Abstract: Hazards such as heatwaves, droughts and floods are often associated with persistent weather patterns. Atmosphere-Ocean General Circulation Models (AOGCMs) are important tools for evaluating projected changes in extreme weather. Here, we demonstrate that 2-day weather pattern persistence, derived from the Lamb Weather Types (LWTs) objective scheme, is a useful concept for both investigating climate risks from multi-hazard events as well as for assessing AOGCM realism. This study evaluates the ability of a Coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 96 publications
0
9
0
Order By: Relevance
“…The residence time approach can characterise episodic, state, and also global stationarity, and is particularly useful for predictability and risk assessment (De Luca et al, 2019;Francis et al, 2020;Berkovic and Raveh-Rubin, 2022). From the time perspective, large values of 𝑅(𝑡) indicate the most stationary periods.…”
Section: Residence Timesmentioning
confidence: 99%
“…The residence time approach can characterise episodic, state, and also global stationarity, and is particularly useful for predictability and risk assessment (De Luca et al, 2019;Francis et al, 2020;Berkovic and Raveh-Rubin, 2022). From the time perspective, large values of 𝑅(𝑡) indicate the most stationary periods.…”
Section: Residence Timesmentioning
confidence: 99%
“…Probabilistic event attribution studies have shown that historical greenhouse gas emissions have already contributed to increased risk of flooding within the context of specific extreme events (quantified for the floods in winter 2013–14, which affected large parts of GB, by Schaller et al, 2016 and Kay et al, 2018). Future GB precipitation and temperature extremes are expected to change in both magnitude and frequency, and even in the type of event (De Luca et al, 2019; Kendon et al, 2014). An increasing frequency of localized summer storms is projected to go hand in hand with more frequent and more widespread droughts (Guillod et al, 2018).…”
Section: Some Key Knowledge Gaps In Our Perceptual Model Of Great Britain's Hydrologymentioning
confidence: 99%
“…The second topic area included seven articles [9][10][11][12][13][14][15] and covered a diverse number of phenomena related to extremes and teleconnections that generally operated on subseasonal and seasonal time scales. The sediment discharge in the Amazon Basin [9] was examined and modelled using in situ and satellite derived information in the river sediment discharge for Amazonia (RSDA) model.…”
mentioning
confidence: 99%
“…The association of natural hazards with persistent weather types occurring over the British Isles in the late 20th century was studied in [12], and this information was then used to determine whether or not these natural hazards would become more common by 2100. This work successfully showed that weather types or analogues are a useful way to project what kind of changes in hazardous weather may occur at the end of the 21st century in different climate change scenarios.…”
mentioning
confidence: 99%
See 1 more Smart Citation